Avoiding Fluorescence Assay Interference—The Case for Diaphorase - Hall, Matthew D. (Assay Drug Dev Technol, 2016)
Fluorescence is utilized as the output for a range of assay formats used in high-throughput screening (HTS). Interference with these assays from the compounds in libraries utilized in HTS is a well-recognized phenomenon, particularly for assays relying on UV excitation such as for direct detection of the oxidoreductase cofactors NADH or NADPH. In this study, we discuss these interference challenges and highlight the specific case of the diaphorase/resazurin system that can be coupled to enzymes utilizing NADH or NADPH. We review the utilization of this assay system in the literature and argue that the diaphorase/resazurin system is underutilized in assay development. It is the authors' hope that this Perspective and the accompanying Technical Brief in this issue will stimulate interest in a robust and sensitive coupling system to avoid assay fluorescence interference.